Rumah susun modular dengan pemanfaatan papan prafabrikasi cross laminated timber panel (CLT), kasus studi: rumah susun Siwalankerto, Surabaya - Wisnu A. Sanjaya; Rumiati Rosaline Tobing (Program Studi Arsitektur Fakultas Teknik Universitas Katolik Widya Mandira, 2019)
Surabaya is the second most populated city in Indonesia. Its ever-growing population creates a problem with its limited number of low-cost housing. Seeing how slow the progress of constructing low cost vertical housing to meet the demands, it requires a faster and more efficient way. By using a modular construction method, this paper tries to analyze the benefit of using an alternate material such as prefabricated CLT (Cross Laminated Timber) panel. CLT panel shows a high potential in creating a better construction that is more environmentally friendly while still benefiting from a faster and lower cost by overall. Siwalankerto vertical housing was chosen due to its modular style of design and usage of material in its façade that is easier to simulate using a prefabricated material. Its location in Surabaya that is near Gresik where the manufactures capable manufacturing the prefabricated material also make it a great choice. This paper limits itself on construction efficiency and effectiveness simulated towards using prefabricated CLT panel and the effects of said material to the organization of rooms inside the building. © 2019 Wisnu A. Sanjaya, Rumiati Rosaline Tobing